Stoichiometry control and epitaxial growth of AgCrSe2 thin films by pulsed-laser deposition - Yusuke Tajima; Kenshin Inamura; Sebun Masaki; Takumi Yamazaki; Takeshi Seki; Kazutaka Kudo; Jobu Matsuno; Junichi Shiogai (APL Materials, 2025)
We report on epitaxial growth in thin-film synthesis of a polar magnetic semiconductor, AgCrSe2, on a lattice-matched yttria-stabilized zirconia (111) substrate by pulsed-layer deposition (PLD). By using an Ag-rich PLD target to compensate for Ag deficiency in thin films, the nucleation of impurity phases is suppressed, resulting in the c-axis-oriented and single-phase AgCrSe2 thin film. Structural analysis using x-ray diffraction and cross-sectional scanning transmission electron microscopy reveals epitaxial growth with the presence of both twisted and polar domains. Optical absorbance spectrum and magnetization measurements show an absorption edge at around 0.84 eV and a magnetic transition temperature at 41 K, respectively. These values are consistent with the reported values of direct bandgap and Néel temperature of bulk AgCrSe2, reflecting a single-phase and stoichiometric feature of the obtained film. Our demonstration of epitaxial thin-film growth of AgCrSe2 serves as a bedrock for exploration of its potential thermoelectric and spintronic functionalities at surfaces or heterointerfaces.